The Effect of Home Adaptation, on Development level of 15-60 Months Old Cerebral Palsy Children - Zahra Ghorbanpour-Kalkhoran; Roshanak Vameghi; Seyyed Ali Hosseini; Mehdi Rassafiani; Hamid Dalvand; Pouria Reza-Soltani (University of Social Welfare and Rehabilitation Sciences, 2014)
Objective: The purpose of this study was to determine the impact of home adaptation on developmental level of 15-60 months old cerebral palsy children. Materials & Methods: In this experimental single-blinded study, forty children with cerebral palsy (15-60 months old) were recruited from some of Tehran public or private rehabilitation clinics based on pre-determined inclusion criteria, and after matching for child age, type of clinic referred to (public or private), type of cerebral palsy, IQ score, GMFCS level and number of occupational treatment sessions already provided at the rehabilitation clinic, the children were divided randomly in to two groups: intervention and control. For data collection, a Demographic Information Questionnaire and Ages & Stages Questionnaires ( ASQ) Test were used. Data were collected on two occasions: before the intervention and 3 months after intervention. For intervention, researcher went to the intervention group home and explained educations related to handling for caregivers and adapted home in a 4-hour session. During 3 months, researcher would follow up to implement the intervention.Finally data were analyzed. Results: there were significant differences in developmental level in total of two groups in 3 months after intervention than before intervention (P<0.015). but there were no significant differences in average relation (0.713), gross motor (0.2), fine motor (0.329) and problem solving(0.981) improvement of two groups in 3 months after intervention. But there were significant differences in average socio - personal improvement between two groups (p<0.001) and this was greater in the intervention group. Conclusion: In this study it is concluded that home adaptation and handling training on caregivers in home improves developmental level in 15 -60 months old cerebral palsy children.